2009
DOI: 10.1080/00049530802607605
|View full text |Cite
|
Sign up to set email alerts
|

Exploring how people respond to conflicts between self-interest and fairness: Influence of threats to the self on affective reactions to advantageous inequity

Abstract: Two studies examined how people deal with conflicts between their self-interest concerns and their striving for fairness. Specifically, the affective reactions to outcome arrangements in which people receive better outcomes than comparable other persons, were studied. These arrangements of advantageous inequity constitute situations in which fairness and self-interest concerns are in conflict. Building on the social psychology of the self, it was predicted, and found, in both field and lab experiments that whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…Another boundary condition is that when people are victimized themselves, subsequent feelings of injustice may be associated with the individual self because victimization may lead people to feel that the perpetrator disrespects them for their own unique attributes. Recent empirical studies indeed found associations between justice concerns and individual self-activation when people were targeted themselves by acts of justice or injustice (Loseman, Miedema, Van den Bos, & Vermunt, 2009;Loseman, Van den Bos, & Ham, 2005;Van Prooijen & Zwenk, 2009). These recent findings, in conjunction with the present findings, may suggest an actor-observer difference in the relation between self-construal activation and justice considerations, such that social self-activation increases people's concern for justice when they are observers, and individual self-activation increases people's concern for justice when they are the target of just or unjust acts.…”
Section: Discussionmentioning
confidence: 99%
“…Another boundary condition is that when people are victimized themselves, subsequent feelings of injustice may be associated with the individual self because victimization may lead people to feel that the perpetrator disrespects them for their own unique attributes. Recent empirical studies indeed found associations between justice concerns and individual self-activation when people were targeted themselves by acts of justice or injustice (Loseman, Miedema, Van den Bos, & Vermunt, 2009;Loseman, Van den Bos, & Ham, 2005;Van Prooijen & Zwenk, 2009). These recent findings, in conjunction with the present findings, may suggest an actor-observer difference in the relation between self-construal activation and justice considerations, such that social self-activation increases people's concern for justice when they are observers, and individual self-activation increases people's concern for justice when they are the target of just or unjust acts.…”
Section: Discussionmentioning
confidence: 99%
“…After all, personal uncertainty can be produced by contextual factors that challenge people's certainty about their cognitions, perceptions, feelings, behaviors, and ultimately their certainty about and confidence in their sense of self (Hogg, 2001). This selfcertainty is very important because the self-concept is the critical organizing principle, referent point, or integrative framework for diverse perceptions, feelings, and behaviors (Sedikides & Strube, 1997; see also Loseman, Miedema, Van den Bos, & Vermunt, 2009). The locus of uncertainty can be found in many aspects of the social context, and therefore we are all susceptible to personal uncertainty.…”
Section: Personal Uncertaintymentioning
confidence: 98%
“…I. McGregor, Newby-Clark, & Zanna, 1999; see also Van den Bos & Maas, in press). Regarding equity concerns, Loseman et al (2009) recently found that reminders of personal uncertainty lead people to respond differently toward equity concerns (especially advantageous inequity), thereby suggesting one link between uncertainty and equity concerns. With respect to belongingness to groups, Mike Hogg's research shows convincingly that personal uncertainty may lead people to identify more strongly with their groups, especially if these groups provide strong means to alleviate the uncomfortable feeling that personal uncertainty often is (e.g., Hogg et al, 2007).…”
mentioning
confidence: 98%
“…Finally, there are different mechanisms underlying advantageous inequity and disadvantageous inequity ( Fliessbach et al, 2012 ). Individuals need to deal with incongruences between their sense of fairness and self-interest concerns when they are exposed to an advantageous inequity situation ( Loseman et al, 2009 ). Therefore, we assumed that a psychophysiological interaction (PPI) analysis may confirm increased functional connectivity among brain regions that are related to self-interest and norm violations when subjects are faced with the influence of an advantageous inequity.…”
Section: Introductionmentioning
confidence: 99%